COVD-01. ADAPTATION OF A GAMMA KNIFE ICON STEREOTACTIC RADIOSURGERY PROGRAM IN THE FACE OF A GLOBAL PANDEMIC. (9th November 2020) - Wegner, Rodney; Horne, Zachary; Xu, Linda; Yu, Alexander; Goss, Matthew; Liang, Yun; Sohn, Jason; Colonias, Athanasios; Fuhrer, Russell; Karlovits, Stephen
Abstract: PURPOSE: The COVID-19 pandemic necessitated drastic and rapid changes throughout the field of radiation oncology, some of which were unique to the discipline of radiosurgery. Available guidelines called for reduced frame use, postponing non-urgent cases, and reducing the number of fractions delivered. Our institution enacted many of these guidelines, and herein we show the resultant effect on patient treatments on our Gamma Knife Icon system. METHODS & MATERIALS: In early to mid-March of 2020 our institution rapidly implemented suggested changes according to ASTRO and other consensus guidelines as they relate specifically to stereotactic radiosurgery in the COVID-19 era. We reviewed the GK Icon schedule at our institution between January 01 and April 30, 2020. We documented age, condition treated, technique (frame vs. mask), and number of fractions. We then tabulated and graphed the number of patients, framed cases, and fractions across that time period. RESULTS: Seventy-seven patients were treated on the GK Icon between January and April 2020, for a total of 231 fractions. The number of unique patients per month varied from 18 (April) to 22 (January). Of the 77 patients only 5 were treated using a frame. The number of fractions per month decreased significantly over time, from 70 in January to 36 in April. Likewise, the percentage of single fraction cases increased from 4.5% per month in January to 67% in April. CONCLUSIONS: The results presented here show that it is possible to quickly and efficiently change work flows to allow for reduced fractionation and frame use in the time of a global pandemic. Multidisciplinary cooperation and ongoing communication are integral to the success of such programs.